ANALISIS STRATEGI KOMUNIKASI PEMASARAN TERPADU RESELLER CRYSTAL OF THE SEA - Rusli Akhmad Junaedi (Prodi Ilmu Komunikasi, FISIP, Universitas Muhammadiyah Cirebon, 2025)
This main objective of this study is to evaluate the marketing communication strategy implemented by resellers of the Crystal of the Sea brand produced by PT Urchindize Indonesia as a leading player in packaged healthy food products made from marine animals. This study was conducted by the development of the crystal of the sea brand market capitalization which was established from 2020 to 2023 every year experiencing an increase in market capitalization of up to 69% by implementing a reseller marketing communication strategy through conventional markets and online marketplaces. Reseller is an indirect marketing communication strategy through intermediary agents in the product distribution. This study applied qualitative methods with in-depth interviews, observation, and document analysis techniques to collect data. Data tringulation was used to analyzed the data. The findings of this study are that Crystal of the Sea resellers implement various integrated marketing communication strategies online and offline such as digital marketing through optimizing marketing content, brand activation through the latest product exhibitions, and personal selling by resellers by prioritizing closeness and excellent customer service.